PENDIDIKAN BUDAYA DAN KARAKTER - I Wayan Sugita (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2018)
The current Indonesian national education still faces various problems. The education achievement is still below the expected target. The teaching and learning process at school has not been able to shape the graduates as whole persons who reflect the character and the culture of the nation. The education process still emphasizes andfocuses its outcome on the cognitive aspects. Meanwhile, the affective aspects of the learners which will become the strong basis to live in the community have not been developed optimally. Therefore, education on character and the culture of the nation must be developed at school. The school as the center of change must make serious efforts to provide education based on the character and the culture of the nation. The character and culture of the nation developed at school must be adjusted to the local, regional, and national character and culture. Hence, education on the character and culture of the nation should be developed based on the local wisdom.